Clínica e contemporaneidade, segundo a prata da casa - Mezan, Renato (Percurso, 2013)
Resenha de Flávio C. Ferraz, Lucia B. Fuks e Silvia L. Alonso (orgs.), Psicanálise em Trabalho, São Paulo, Sedes/Escuta, 2012, 275 p.